(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
ملخص: تهدف الدراسة إلى التعرف على وجهة نظر أخصائيي مكتبات جامعة غرداية حول واقع اعتماد نظام إدارة الجودة (ISO 9001) في الخدمات المقدمة إلى المستفيدين، وقد اعتمدنا في هذه الدراسة على المنهج الوصفي، وتم استخدام الإستبيان كأداة للدراسة في جمع البيانات. حيث شملت عينة الدراسة مسح كل أفراد مجتمع الدراسة وهم العاملون على مستوى مكتبات جامعة غرداية، البالغ عددهم (34) مكتبياً خلال الفترة الممتدة بين شهر نوفمبر إلى ديسمبر 2020. وقد أظهرت الدراسة وجود ممارسة لنظام إدارة الجودة (ISO 9001) في الخدمات المقدمة بمكتبات جامعة غرداية من وجهة نظر العاملين بها تتم بدرجة متوسطة وبشكل متفاوت فيما بين أبعاد نظام إدارة الجودة. كلمات دالة : إدارة الجودة، ISO 9001، جودة الخدمة، خدمات المكتبة الجامعية. Abstract: The study aims to identify the point of view of the librarians of the University of Ghardaia about the reality of adopting the quality management system (ISO 9001) in the services provided to the beneficiaries, and we have relied in this study on the descriptive approach, and the questionnaire was used as a study tool in data collection. The study sample included a survey of all members of the study community, who are working at the libraries of the University of Ghardaia, whose number is (Thirty-four) librarians during the period between November and December 2020. The study showed the existence of a moderate practice degree of the quality management system (ISO 9001) in the services provided by Libraries of The University of Ghardaia from the point of view of its librarians, which is carried out to a varying degrees between the dimensions of the quality management system. Key words: Quality management, ISO 9001, Quality service, University library services.